Association between high levels of gynoid fat and the increase of bone mineral density in women. (3rd March 2020) - Aedo, S.; Blümel, J. E.; Carrillo-Larco, R. M.; Vallejo, M. S.; Aedo, G.; Gómez, G. G.; Campodónico, I.
Abstract: Introduction: In women, bone mineral density (BMD) is related to age, estrogenic action, and appendicular skeletal muscle mass (ASMM). The gynoid fat distribution is linked to estrogenic action. Objective: This study aimed to assess whether an increase of gynoid fat is associated with high BMD independent of age and ASMM. Methods: An observational study was performed in women aged between 20 and 79 years. Fat mass, ASMM, and BMD were measured with dual-energy X-ray absorptiometry. The binned scatterplots and multivariate linear regression models were used to study the relationship between hip BMD and age, height, android fat, gynoid fat, and ASMM. Results: Of 673 women invited, 596 accepted to participate. Their mean age was 55.4 ± 12.8 years, weight 63.4 ± 9.4 kg, height 1.61 ± 0.06 m, body mass index 24.54 ± 3.59 kg/m 2, average hip BMD 0.914 ± 0.122 g/cm 2, android fat 2.12 ± 0.83 kg, gynoid fat 4.54 ± 1.07 kg, and ASMM 15.15 ± 1.97 kg. The final regression model included age (linear coefficient −0.004; 95% confidence interval [CI]: −0.005 to −0.003; p  < 0.001), ASMM (linear coefficient 0.013; 95% CI: 0.009 to 0.018; p  < 0.001), and gynoid fat (linear coefficient 0.013; 95% CI: 0.005 to 0.022; p  < 0.002). Conclusion: Gynoid fat is associated with BMD in the hip independently of age and ASMM.